Speech and language development in children with 49, XXXXY syndrome. Issue 12 (28th July 2020) - Samango‐Sprouse, Carole A.; Lasutschinkow, Patricia C.; McLeod, Michael; Porter, Grace F.; Powell, Sherida; St. Laurent, Jillyan; Sadeghin, Teresa; Gropman, Andrea L.
Abstract: 49, XXXXY is the rarest X and Y chromosomal variation and is frequently characterized by expressive and receptive language dysfunction, low muscle tonus, and intellectual deficits. Due to the low incidence of this disorder, comprehensive studies analyzing the specific aspects of the speech and language phenotype in these boys have been uncommon. This is the first in‐depth investigation of the speech and language profiles in a large cohort of boys with 49, XXXXY. Based on the clinical judgment of speech and language pathologists, there was an increased incidence (91.8%) of Childhood Apraxia of Speech (CAS), which has not been previously described in this disorder. In preschool boys, some significant differences were demonstrated between boys who received early hormonal treatment ( n = 16) and untreated boys ( n = 4) on the language scales ( p = .047) on the Bayley Scales of Infants and Toddlers, as well as significant differences between treated ( n = 13) and untreated boys ( n = 8) on the Expressive One Word Picture Vocabulary Test ( p = .008). No significant differences between treatment groups were found in school age children, however, treated groups demonstrated less discrepancies between expressive and receptive language. More research and larger samples are needed to determine the extent of the impact of testosterone treatment on boys with 49, XXXXY. This study identifies CAS as a potential explanation for the significant expressive language dysfunction and subsequent behavioral dysfunction. These findings may assist in facilitating more targeted treatment and improved outcomes for boys with 49, XXXXY.